City of Bits Space, Place, and the Infobahn - Mitchell, William J. (The MIT Press, 1996)
Entertaining, concise, and relentlessly probing, City of Bits is a comprehensive introduction to a new type of city, an increasingly important system of virtual spaces interconnected by the information superhighway. William Mitchell makes extensive use of practical examples and illustrations in a technically well-grounded yet accessible examination of architecture and urbanism in the context of the digital telecommunications revolution, the ongoing miniaturization of electronics, the commodification of bits, and the growing domination of software over materialized form.